Stress distribution and patient satisfaction in flexible and cast metal removable partial dentures: Finite element analysis and randomized pilot study - Niraj Kumar; Dheeraj Kumar Koli; Veena Jain; Aditi Nanda (Journal of Oral Biology and Craniofacial Research)
Purpose: To compare stress distribution in polyacetyl based flexible RPD (FRPD) with cast metal RPD (CRPD) by using three-dimensional finite element analysis (FEA) and patient satisfaction by using OHIP-14 questionnaire in participants with Kennedy's class I partially edentulous mandibular arch rehabilitated with CRPD and FRPD. Material and methods: For FEA, 3D models of Kennedy's class I partially edentulous mandibular arch, CRPD in chrome-cobolt alloy, and polyacetyl based FRPD were geometrically modelled and subjected to a vertical load of 100 ​N bilaterally. The in vivo comparison of satisfaction was assessed by enrolling 22 participants with Kennedy's class I partially edentulous mandibular arch. After randomization, 11 participants were rehabilitated by CRPD (group C), and 11 participants by polyacetyl based FRPD (group F). OHIP-14 questionnaire in Hindi language was filled at 1 week and 1 year after denture insertion. Results: Von Mises stress distribution in CRPD was maximum in mesial rest seat of the primary abutment (100 ​MPa) and minimum for edentulous ridge (7 ​MPa on bone and 6 ​MPa on mucosa). Von Mises stress distribution for polyaccetyl based FRPD was maximum in ridge (25 ​MPa) and minimum in periodontal ligament of the second premolar (3 ​MPa). Patient satisfaction in group F was significantly more than in group C at end of 1 year (P ​= ​.0158). Conclusion: FRPD is useful in periodontally compromised abutment teeth and CRPD in resorbed ridge conditions. Patient satisfaction is more with polyacetyl based flexible RPD when compared with cast metal RPD at the end of 1 year.